Expanding the phenotypic associations of globular glial tau subtypes. Issue 1 (8th April 2016) - Burrell, James R.; Forrest, Shelley; Bak, Thomas H.; Hodges, John R.; Halliday, Glenda M.; Kril, Jillian J.
Abstract: Introduction: Clinicopathologic correlation in non‐Alzheimer's tauopathies is variable, despite refinement of pathologic diagnostic criteria. In the present study, the clinical and neuroimaging characteristics of globular glial tauopathy (GGT) were examined to determine whether subtyping according to consensus guidelines improves clinicopathologic correlation. Methods: Confirmed GGT cases (n = 11) were identified from 181 frontotemporal tauopathy cases. Clinical and neuroimaging details were collected, and cases sub‐typed according to the consensus criteria for GGT diagnosis. Relationships between clinical syndrome and GGT subtype were investigated. Results: In total, 11 patients (seven males, four females, mean age = 67.3 +/− 10.6 years) with GGT were included. Most, but not all, presented with behavioral variant frontotemporal dementia, but none had amyotrophic lateral sclerosis. Subtyping of GGT proved to be difficult and did not improve clinicopathologic correlation. Discussion: Sub‐classification of GGT pathology may be difficult and did not improve clinicopathologic correlation. Better biomarkers of tau pathology are needed.